VARIABILITY STUDIES IN SPROUTING BROCCOLI HYBRIDS ARIABILITY STUDIES IN SPROUTING BROCCOLI HYBRIDS (BRASSICA OLERACEA L. VAR. ITALICA PLENCK) UNDER MID HILLS OF NORTH-WESTREN HIMALAYAS - SHIWANI, KUMARI; KATOCH, VIVEKA; SHARMA, AKHILESH (The Bioscan, 2016)
Significant differences were observed among genotypes in sprouting broccoli suggesting sufficient genetic variability for yield and other yield related characters. The highest estimates of phenotypic coefficient of variation and genotypic coefficient of variation were observed for number of spears per plant (42.85 % and 83.93 %) followed by weight of spears per plant (40.46 % and 35.31 %) and terminal head weight per pant (33.60 % and 31.96 %). High heritability coupled with high genetic advance was observed for characters viz., terminal head weight per plant (90.46 % and 62. 61 %), marketable yield per plant (89.44 % and 56.51 %), number of spears per plant (82.56% and 72.86 %), harvest index (77.03 % and 35.35 %) and weight of spears per plant (76.17 % and 63.50 %). These high estimates suggest substantial variability for the characters thereby ensuring ample scope for improvement of these characters through direct selection. On the basis of genetic divergence, sixteen genotypes were grouped into three clusters. Altar and Indica were found to be the most diverse genotypes and offer promise as a breeding stock to be used in hybridization for obtaining transgressive segregants for further exploitation in broccoli improvement programme.